Lysosomal polyamine storage upon ATP13A2 loss impairs β-glucocerebrosidase via altered lysosomal pH and electrostatic hydrolase-lipid interactions - Madhuja Samaddar; Gabriel A. Fitzgerald; Ann Hong Nguyen; Sonnet S. Davis; Shourya Jain; Jian Guo; Nicholas E. Propson; Bettina van Lengerich; Yajuan Shi; Srijana Balasundar; Lionel Rougé; Jamal Alkabsh; et al. (Cell Reports)
Summary: ATP13A2 is an endolysosomal polyamine transporter mutated in several neurodegenerative conditions involving lysosomal defects, including Parkinson’s disease (PD). While polyamines are polybasic and polycationic molecules that play pleiotropic cellular roles, their specific impact on lysosomal health is unknown. Here, we demonstrate lysosomal polyamine accumulation in ATP13A2 knockout (KO) cell lines and human induced pluripotent stem cell (iPSC)-derived neurons. Primary polyamine storage caused secondary storage of lysosomal anionic phospholipid bis(monoacylglycero)phosphate (BMP) and an age-dependent increase in the β-glucocerebrosidase (GCase) substrate glucosylsphingosine in Atp13a2 KO brains. Polyamine accumulation inhibited lysosomal GCase activity in cells, and this was reversed by lysosome reacidification or BMP supplementation. A liposome-based GCase assay utilizing physiological substrates demonstrated dose-dependent inhibition of BMP-stimulated GCase activity by polyamines, in part via a pH-independent, electrostatics-based mechanism. Therefore, excess polyamine compromises lysosomes by disrupting pH and electrostatic interactions between GCase and BMP that enable efficient substrate hydrolysis, potentially clarifying pathogenic mechanisms and suggesting convergence on PD-relevant pathways.